Gut symbiont enhances insecticide resistance in a significant pest, the oriental fruit fly Bactrocera dorsalis (Hendel). Issue 1 (December 2017) - Cheng, Daifeng; Guo, Zijun; Riegler, Markus; Xi, Zhiyong; Liang, Guangwen; Xu, Yijuan
Abstract Background Symbiotic bacteria affect insect physiology and ecology. They may also mediate insecticide resistance within their hosts and thereby impact pest and vector control practices. Here, we document a novel mechanism of insecticide resistance in which a gut symbiont of the tephritid pest fruit flyBactrocera dorsalis enhances resistance to the organophosphate insecticide trichlorphon. Results We demonstrated that the gut symbiontCitrobacter sp. (CF-BD) plays a key role in the degradation of trichlorphon. Based on a comparative genomics analysis with otherCitrobacter species, phosphatase hydrolase genes were identified in CF-BD. These CF-BD genes had higher expression when trichlorphon was present.Bactrocera dorsalis inoculated with isolated CF-BD obtained higher trichlorphon resistance, while antibiotic-treated flies were less resistant confirming the key role of CF-BD in insecticide resistance. Conclusions Our findings suggest that symbiont-mediated insecticide resistance can readily develop inB. dorsalis and may represent a more widely relevant insecticide resistance mechanism than previously recognized.